Altered ErbB4 splicing and cortical parvalbumin interneuron dysfunction in schizophrenia and mood disorders. (November 2018) - Chung, Daniel; Chung, Youjin; Bazmi, H.; Lewis, David
Abstract Working memory requires the activity of parvalbumin (PV) interneurons in the dorsolateral prefrontal cortex (DLPFC). Impaired working memory and lower PV expression in the DLPFC are reported in schizophrenia and to a lesser degree in mood disorders. We previously proposed that activity-dependent PV expression is lower in schizophrenia due to a shift in the splicing of erb-b2 receptor tyrosine kinase 4 (ErbB4) transcripts from major to inactive minor variants that reduces excitatory drive to PV interneurons. Here, we tested the hypothesis that the degree of major-to-minor shift in ErbB4 splicing predicts the level of PV expression across schizophrenia and mood disorders. Levels of ErbB4 splice variants and PV mRNA were quantified by PCR in the DLPFC from 40 matched tetrads (N = 160 subjects) of schizophrenia, bipolar disorder (BD), major depressive disorder (MDD), and unaffected comparison subjects. Relative to unaffected comparison subjects, the magnitude of increases in minor variant levels and decreases in major variant levels was greatest in schizophrenia, intermediate in BD, and least in MDD. The same rank order was present for the magnitude of increases in the composite splicing score, which reflects the degree of major-to-minor shift across all ErbB4 splice loci, and for the magnitude of deficient PV expression. Finally, the composite splicing score negatively predicted PV expression across all subject groups. Together, these findings demonstrate a shared relationship between ErbB4 splicing and PV expression and suggest that scaling of the major-to-minor shift in ErbB4 splicing may influence the severity of deficient PV interneuron activity across diagnoses.